2020
DOI: 10.3928/00220124-20200216-08
|View full text |Cite
|
Sign up to set email alerts
|

Current State and Influencing Factors of Nurse Resilience and Perceived Job-Related Stressors

Abstract: Background: Resilience is a characteristic and skill that nurses can learn. This study examined the current state and influencing factors of nurse resilience and nurse perceived job-related stressors. Method: This cross-sectional survey study was conducted at a university-affiliated hospital in China between May and August 2018. The Connor-Davidson Resilience Scale was used to measure nurse resilience. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
1
21
2
Order By: Relevance
“…J. Zhang et al, 2019) such as self-esteem, fatigue, psychological statuses (depression) (K. Xu et al, 2019), and overall physical and mental health (Ding et al, 2017;Smith & Yang, 2017). Several studies have shown nurses displaying low resilience (Leng et al, 2020;Peng et al, 2017;. In contrast, our study indicates resilience scores of 87.04 ± 22.78, markedly higher than the results of previous studies.…”
Section: Discussioncontrasting
confidence: 56%
“…J. Zhang et al, 2019) such as self-esteem, fatigue, psychological statuses (depression) (K. Xu et al, 2019), and overall physical and mental health (Ding et al, 2017;Smith & Yang, 2017). Several studies have shown nurses displaying low resilience (Leng et al, 2020;Peng et al, 2017;. In contrast, our study indicates resilience scores of 87.04 ± 22.78, markedly higher than the results of previous studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Examining the relationship between nurses' resilience and demographic characteristics, the study showed that the level of education, marital status, gender, work experience and work shifts with resilience did not significantly differ. There was a significant relationship between nurses' resilience and age, years of experience, clinical rank and education (Leng et al 2020). A study by Ren et al (2018) showed that female nurses, with a high level of education and position and no night shifts, had high resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses were selected based on their high levels of clinical performance and resilience scores based on the Chinese version Conner‐Davidson Mental Resilience Scale 8,9 screened by the hospital. The average resilience score of the nurses selected was 79.34 ± 11.98, while the average rating of nurses' resilience was 61.35 ± 13.12 in the hospital 10 . The inclusion criteria were that nurses (a) had at least 1 year of nursing experience, (b) took care of patients with COVID‐19 in the ICU for at least a month, and (c) and were willing to join the study.…”
Section: Methodsmentioning
confidence: 99%